#TITLE_ALTERNATIVE# - PRASETYA AJI (NIM 20206009), MAHARDIKA
Research on iron oxides is still progressing today. Based on its unique response to magnetic fields, magnetite has been used widely both as research as well as industrial materials. Iron oxides can be found easily in common materials, such as in mill scale and iron sand. The extensive distribution and volume of iron sand deposits in Indonesia is very attractive economically. As naturally occurring materials, the characteristics of iron sand depend strongly on natural conditions and, therefore, magnetic minerals of iron sand tend to be heterogeneous. In this research, magnetite was grown from iron sand by means of precipitation method. The objective of this research is to acquire magnetite grains of uniform size, predictable and preferable magnetic properties. Other than that, this research is also intended to check whether precipitation is input sensitive. The precipitation commences with a production of ferric chloride salt solution that contain Fe3+ and Fe2+ ions required to form magnetite in precipitation process. The solution was made by mixing extracted magnetic minerals from iron sand with hydrochloric acid (HCl). Adding a solution of ammonium base (NH4OH) slowly in the ferric chloride salt produces a dark deposit that respond to magnetic field. This dark deposit was then transformed into powder by heating. In this research, we varied the concentration of ferric chloride salt as well as the concentration of ammonium base to find the optimum magnetic properties of the dark deposits. The amount of deposits and their magnetic properties varies depending on the concentrations of the salt and the base. Higher concentration of salt solution and base solution tend to produce larger amount of deposits as the abundance of Fe2+ and Fe3+ increases. However, deposits with stronger magnetic properties were produced by lower concentration of both salt and base solution. Identification of magnetite in the deposits was carried out using the measurements of IRM (isothermal remanent magnetization). Meanwhile, estimation of grain size was carried out using the measurements low field magnetic susceptibility and anhysteretic susceptibility. Saturation of IRM at applied field of less than 300 mT indicates that the main magnetic mineral in the deposits is truly magnetite. Plots of low field versus anhysteretic susceptibilities show that each set of salt and base concentration produces grains of almost uniform in size. Higher concentrations of salt and base solution tend to produce smaller magnetite grains. Uniform grain sizes produced by precipitation in this research indicate that precipitation is insensitive to input. This means that precipitation can use affordable raw materials.